Peran Harga Diri Terhadap Ketidakpuasan Bentuk Tubuh Remaja Perempuan - Anggia Kargenti Evanurul Marettih; Ikhwanisifa Ikhwanisifa; Yuli Widiningsih; Cindy Puspa Yovanny (Psychopolytan : Jurnal Psikologi, 2024)
Body dissatisfaction is a serious phenomenon that requires precautions because it generates a serious of health complications, including impaired well-being. Self-esteem is one of the factors that can predict body dissatisfaction.This study aims to determine the role of self-esteem to body dissatisfaction in adolescent female. There are 250 adolescents female determined in this study using a purposive sampling technique. The BSQ-34 from Cooper et al. (1987) was applied to assess body dissatisfaction and the state self-esteem scale from Heatherton & Polivy (1991) was used to assess self-esteem. The regression model indicates r= -0.345, F= 16,996, B= -0,321 (p<0,000), which is means that self-esteem has a very significant role in predicting body dissatisfaction in adolescent females. These findings indicate that if adolescents have high self-esteem then dissatisfaction with their bodies is low, conversely if adolescents' self-esteem is low then adolescents will experience high body dissatisfaction. Appearance is the aspect of self-esteem that contributes the most to predicting body dissatisfaction, with r = -0,386,( p <0,000). Negatif appraisal of physical appearance can cause highest body dissatisfaction in female. That is the reason why it is important to have a possitive appraisal to avoid body dissatisfaction in adolescent female.